Kajian Peran Kepolisian terhadap Tindak Pidana Pelanggaran Merek dengan Memperdagangkan Barang tanpa Seizin Pemilik Merek yang Terdaftar - Abel Yumay; Ichwan Setiawan; I Gusti Agung Ngurah (PT Elaborium Elevasi Indonesia, 2023)
Unlike copyrights, trademarks must first be registered in the General Trademark Register. This is useful so that every producer, entrepreneur, or trader can be legally protected with respect to trademark rights over their goods. Trademark Law Number 15 of 2001, which requires the mark to be registered. If the trademark has been registered legally, in the event of a violation of the rights to the mark, the legal owner or rights holder can file a claim by taking legal action as stated in Article 76 of the Law on Marks and Trademarks 20 (2016) concerning geographical indications. Indeed, the protection of brand rights for brand owners in Indonesia has recently decreased. In fact, trademark infringement is still common. Well-known trademarks are generally inseparable from intellectual property rights violations, such as counterfeiting, imitation, and reputational carpooling. This journal uses normative legal research methods. Legal writing is research that examines legal materials, positive legal provisions, legal principles, and legal doctrine in order to answer the legal issues at hand. The problem approach used is the statutory approach. The technique of tracing legal materials uses a literature study technique as well as an analysis of the study using qualitative analysis.Based on the research results, the authors can conclude that their rights still have protection against criminal acts of trademark infringement. Likewise, the police also play a fundamental role in dealing with criminal acts of trademark infringement by trading goods without the permission of the registered trademark owner. There are three types of police handling of trademark infringement: pre-emptive, preventive, and repressive measures.